Exploring the Dimensions of Service Quality and Customer Satisfaction of Mixue Product - Slamet Heriwinarno; Lela Elvira (MultiTech Publisher, 2023)
This study aims to explain the effect of applying the service dimension on customer satisfaction. Quality service is a comparison between the service felt by customers and the quality of service that customers expect through its dimensions. Research is descriptive and quantitative, looking for causality between the variables studied. This research focused on 100 sample people who were customers of Mixue start-up products located in Depok, West Java, and surrounding areas. Data collection used questionnaires and was obtained using the SEM method of path analysis. The results showed that of the five dimensions of service, one, namely responsiveness, did not have a significant influence on customer satisfaction. The validity test results show that all question items are valid, and the research model is feasible or reliable to use. This study also resulted in a squared multiple correlation (R2) value of 0.604, where customer satisfaction can be explained by service dimensions of 60.4%.